2011
DOI: 10.1007/s10803-011-1264-3
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and Perceptual Measurement of Expressive Prosody in High-Functioning Autism: Increased Pitch Range and What it Means to Listeners

Abstract: Are there consistent markers of atypical prosody in speakers with high functioning autism (HFA) compared to typically-developing speakers? We examined: (1) acoustic measurements of pitch range, mean pitch and speech rate in conversation, (2) perceptual ratings of conversation for these features and overall prosody, and (3) acoustic measurements of speech from a structured task. Increased pitch range was found in speakers with HFA during both conversation and structured communication. In global ratings listener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(146 citation statements)
references
References 21 publications
8
128
1
9
Order By: Relevance
“…6, No. 4;2016 In these tables we used s and q after duration, amplitude and tilt s and q being abbreviations for statements and questions. The number (N) of the autistic children who could produce the questions was 14.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…6, No. 4;2016 In these tables we used s and q after duration, amplitude and tilt s and q being abbreviations for statements and questions. The number (N) of the autistic children who could produce the questions was 14.…”
Section: Resultsmentioning
confidence: 99%
“…6, No. 4;2016 intonation and the Tilt Model of Intonation, which provided a complete mapping between acoustics and phonology and an exact acoustic analysis, were used. In the first statistic hypothesis, the durations of statements and questions were surveyed, and the result in Table 1 indicated that there is no significant difference in the two kinds of sentences between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that children with childhood apraxia of speech may demonstrate "reduced range of or variable (perceived) pitch, as well as reduced range of or variable (perceived) loudness, (which) gives the listener the impression of monotone, monoloud speech, respectively" (American Speech-Hearing-Language Association, 2007, p. 20). Prosodic disturbances have also been noted in the speech of children with high-functioning autism; specifically, greater SFF range in conversational speech compared to typically developing peers (Nadig & Shaw, 2012). Considering all of the disorders that may involve abnormal measured or perceived vocal variability, objective data on frequency variability in typically developing children may help the speech-language pathologist in diagnosing and tracking changes in children with a variety of communication disorders.…”
mentioning
confidence: 99%